Combined effects of gamma irradiation and carbon dioxide enrichment on physiological traits and flavonoid contents Centella asiatica L - Moghaddam, Sina Siavash (2011)
The study was conducted to investigate the effects of gamma irradiation on secondary metabolite biosynthesis based on flavonoid, and to provide valuable information on the utilization of beneficial effects of gamma radiation in plant cell culture system. The work also determined the combined effects between gamma irradiation and CO2 enrichment on physiological characteristics and flavonoid compounds of Centella asiatica as medicinal herb. Turning to the experimental evidence, significant differences were observed in morphological characters, physiological and total flavonoid contents of eight accessions. Total flavonoid content in the leaf was observed to be highest compared with petiole and root in CA23 (9.33± 0.04mg/g DW) and lowest in CA03 (3.17± 0.01mg/g DW). Meanwhile, CA23 was found to have highest net photosynthesis (PN) and leaf area. Time to harvest was observed to be an important factor for accumulation of total flavonoid content in the plants and 6 weeks after planting was recorded to be the best for all accessions. In tissue culture experiments, analysis of variance for shoot regeneration from C. asiatica nodal explants which cultured on Murashige and Skoog (MS) and shoot media (Duchefa) supplemented with various concentrations of BAP in combination with NAA revealed that frequency of responding explants increased markedly with an enhancing in the concentration of BAP up to 2mg/l in combination of 0.1mg/l NAA in Duchefa medium as well as soaking in TDZ. The highest shoot multiplication, node/explant and leaf/explants of C.asiatica were achieved with soaking in (TDZ) at a concentration of 5mg/l for 2 hours. The results of this investigation show that, full-strength MS medium was better than half-strength MS medium for root initiation. A comparison by Duncan’s method revealed optimum frequency 95% in shoots cultured on full-strength MS containing 0.5mg/l IBA. The acclimatized plantlets were successfully established with 85% and 77% survival for CA23 and CA03 accessions respectively. The results for radiation sensitivity test based on survival percentage of irradiated and non-irradiated plantlets demonstrated that significant reduction in survival percentage was observed with increasing gamma dosage. For the survival percentage of irradiated nodals to reach 50%, the gamma dosage administered was 60Gy for CA03 and 40Gy for CA23. The most obvious findings to emerge from this study are that, gamma irradiation induced various physiological and biochemical alterations in plants. Biochemical tests unfolded that the irradiated accessions displayed higher total flavonoid content than the non-irradiated ones. The chromatograms obtained from High Performance Liquid Chromatography (HPLC) study revealed that methanolic extracts of Centella asiatica under the irradiation treatments displayed significantly variable compositions of flavonoid compounds. Interestingly, among the flavonoids detected, the concentration of rutin in the leaf extracts was found to be the highest (1.51±0.00014mg/g DW) from those of the other flavonoids. In addition, after rutin, in irradiated plants, fisetin (in CA03) and naringin (in CA23) were detected in the highest amount. Photosynthetic pigments were declined through gamma irradiation with concomitant loss of the photosynthetic ability. The results of this study indicated that under gamma conditions the Malondialdehyde (MDA)(as an indicator of free radicals) and flavonoid contents increased and the Fv/Fm declined concomitantly. This study also investigated that elevated CO2 as excess carbon promoted photosynthesis rate and increased the growth of C.asiatica, as well as stimulated the defense mechanism through boosting flavonoid content. The evidence from this study elucidated that the 4- hours CO2 enrichment at 800μmol/mol signified that there were no significant differences in the measured traits with the exception of carbohydrates, where high level of carbohydrate accumulation caused restriction in potential of net photosynthesis in irradiated and non-irradiated plants of Centella asiatica. These findings enhance our understanding about metabolic engineering of flavonoid pathway which gamma and CO2 concomitantly and synergistically resulted in boosting flavonoid concentration. Although CO2 enrichment ameliorated the adverse effects of gamma on photosynthesis, the plant also benefits from gamma irradiation to significantly boost flavonoids components.